Legal Certainty in the Re-Norming of Article 66(1) of the Notary Law - Izza Safira; M. Hamidi Masykur; Letiza Dessy Andreassari (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
This study aims to evaluate the consistency of legal certainty and the constitutional implications resulting from the re-norming of the phrase